2021
DOI: 10.7326/m21-0857
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydroxychloroquine, Remdesivir, and Dexamethasone Among Adults Hospitalized With COVID-19 in the United States

Abstract: Many drugs have been used in the treatment of COVID-19 since the beginning of the pandemic. In a large multicenter cohort study of 137 870 individuals hospitalized with confirmed or suspected COVID-19, investigators assessed temporal and institutional variation in the use of 3 of the most widely used drugs: hydroxychloroquine, remdesivir, and dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
(29 reference statements)
1
35
0
Order By: Relevance
“…There was a higher frequency of corticosteroids in those requiring invasive mechanical ventilation. This was like the finding from another study from that time, although they used dexamethasone [ 36 ]. Regardless of methylprednisolone use or not, patients with VTE had higher median d-dimers compared to those with no VTE.…”
Section: Discussionsupporting
confidence: 82%
“…There was a higher frequency of corticosteroids in those requiring invasive mechanical ventilation. This was like the finding from another study from that time, although they used dexamethasone [ 36 ]. Regardless of methylprednisolone use or not, patients with VTE had higher median d-dimers compared to those with no VTE.…”
Section: Discussionsupporting
confidence: 82%
“…In inpatient settings, Black inpatients received remdesivir more often, and Black, Asian, and Hispanic inpatients received dexamethasone less often than did comparison groups. This could indicate racial and ethnic differences in clinical indications for medication use (e.g., age distribution and prevalence of comorbidities) or could be reflective of varying prescribing practices, protocols, and drug access by institutions that serve populations of different racial and ethnic distributions (7).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the landmark RECOVERY trial that involved confirmed patients of COVID-19 showed that the use of dexamethasone resulted in reduced mortality and need of mechanical ventilators or oxygen supply ( Hamilton et al., 2021 ). Based on this trial, dexamethasone was approved among critically ill patients, either alone or in combination with remdesivir ( Vetter et al., 2020 ; Mehta et al., 2021 ). Interferon-β-1a, a cytokine, exhibits an immunogenic response against viral infection ( Yuen et al., 2020 ).…”
Section: Susceptibility Of Coronavirus Disease 2019 To Clinically Used Drugsmentioning
confidence: 99%